2017
DOI: 10.1002/jez.b.22732
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Morphology of the Penis and Clitoris in Four Species of Moles (Talpidae)

Abstract: The penile and clitorial anatomy of four species of Talpid moles (broad-footed, star-nosed, hairy-tailed, and Japanese shrew moles) were investigated to define penile and clitoral anatomy and to examine the relationship of the clitoral anatomy with the presence or absence of ovotestes. The ovotestis contains ovarian tissue and glandular tissue resembling fetal testicular tissue and can produce androgens. The ovotestis is present in star-nosed and hairy-tailed moles, but not in broad-footed and Japanese shrew m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Moreover, she is certainly not alone in possessing a hypertrophied clitoris (e.g. proboscideans, elephant (Glickman et al 2005); primates including platyrrhines (Campbell 2017, Carosi et al 2020, strepsirrhines and others (Hill 1953, Dixson 1998, Drea & Weil 2008; viverrids (Hawkins et al 2002); talpids (Sinclair et al 2017)), suggesting that successful birth via this structure is what, ironically, derails notions about her femininity. These incongruities illustrate the inadequacy of a male-centric definition of reproductive biology.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, she is certainly not alone in possessing a hypertrophied clitoris (e.g. proboscideans, elephant (Glickman et al 2005); primates including platyrrhines (Campbell 2017, Carosi et al 2020, strepsirrhines and others (Hill 1953, Dixson 1998, Drea & Weil 2008; viverrids (Hawkins et al 2002); talpids (Sinclair et al 2017)), suggesting that successful birth via this structure is what, ironically, derails notions about her femininity. These incongruities illustrate the inadequacy of a male-centric definition of reproductive biology.…”
Section: Discussionmentioning
confidence: 99%
“…In the spotted hyena male and female phalluses are approximately the same size in adulthood (Cunha et al, 2014), and penile and clitoral growth (length) has been shown to be androgen-independent in spotted hyenas (Glickman et al, 1992; Glickman et al, 1998). The prepuce of several species of moles is of similar size in both males and females (Sinclair et al, 2016b). In these examples various aspect of male external genitalia are only slightly larger than their female counterparts, raising the possibility that certain aspects of development/growth of male external genitalia are androgen-independent.…”
Section: Discussionmentioning
confidence: 99%
“…The internally positioned clitoris of broad-footed moles is defined by a U-shaped clitoral epithelial lamina similar to that of the mouse clitoris (Cunha et al, 2019a;Martin-Alguacil et al, 2008b;Sinclair et al, 2016c). These findings of mole external genitalia were confirmed in a subsequent paper on the comparative anatomy of 4 species of moles (Sinclair et al, 2016b). As in mice, adult size of the perineal appendage is slightly greater in male than female moles.…”
Section: Mole External Genitaliamentioning
confidence: 82%